2015
DOI: 10.1016/j.foodpol.2014.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Technical and allocative efficiency of irrigation water use in the Guanzhong Plain, China

Abstract: a b s t r a c tDue to increasing water scarcity, accelerating industrialization and urbanization, efficiency of irrigation water use in Northern China needs urgent improvement. Based on a sample of 347 wheat growers in the Guanzhong Plain, this paper simultaneously estimates a production function, and its corresponding first-order conditions for cost minimization, to analyze efficiency of irrigation water use. The main findings are that average technical, allocative, and overall economic efficiency are 0.35, 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 36 publications
(34 reference statements)
2
41
1
1
Order By: Relevance
“…On the other hand, the "income effect" can increase IWE. For instance, Tang et al has reported a significant positive relationship between income and technical efficiency of irrigation water use [13]. First, off-farm income can be used to finance irrigation investment, which helps farmers get higher IWE.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, the "income effect" can increase IWE. For instance, Tang et al has reported a significant positive relationship between income and technical efficiency of irrigation water use [13]. First, off-farm income can be used to finance irrigation investment, which helps farmers get higher IWE.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Estimating Equation (4) generates direct estimates of input-oriented technical inefficiency. Most previous studies have used an output-oriented approach and derived input technical efficiency from the regression results [9][10][11][12][13]. Moreover, we can employ the one-step approach by estimating Equation (4) together with Equation (5), which is expressed as…”
Section: Empirical Specificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Although technical and groundwater use efficiency provides important information about the management practices of farmers, these indicators do not explain farmers' ability to allocate irrigation water and other inputs to their cost-minimising input proportions [25]. Information about allocative efficiency and its determinants provides crucial help to policy makers in devising policies for expediting rural development and increasing farm income [26,27].…”
Section: Introductionmentioning
confidence: 99%